Peran Mediasi Toleransi Risiko Dalam Analisis Determinasi Keputusan Investasi Mahasiswa Kota Denpasar - Prabandari Tri Putri, I Gusti Agung; Yuliana Ria Sawitri, Ni Putu; Wijaya, Bagus Arya; Sudiyani, Ni Nyoman (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2024)
Student investment decisions are financial behavior and a form of awareness to achieve financial freedom and well-being at a young age. This study aims to examine the mediating role of student risk tolerance in making investment decisions based on financial literacy, overconfidence bias, and representative bias. The population included students from higher education in Denpasar City who invested in stocks, with non-probability sampling methods and purposive sampling techniques set the number of sample of as many as 105 respondents. Testing of research data using SEM PLS technique. The result proved that financial literacy has a negative and significant effect on investment decisions; overconfidence bias and risk tolerance have a positive and significant effect on investment decisions; while representative bias does not have a significant effect on investment decisions. Overconfidence bias has a positive and significant effect on risk tolerance but financial literacy and representative bias do not have a significant effect on risk tolerance. This study was able to prove that overconfidence bias has a positive and significant effect on investment decisions with risk tolerance as mediation, while risk tolerance is unable to mediate the influence of financial literacy and representative bias on investment decisions.